Cultive tissue of Salvia hispanica L. - Arfux, Claudia Regina Baur; Menegati, Celia de Fátima; Silva, Renata Moreira da; Rondon, Josimara Nolasco; Gabriel, Valdinez; Costa, Francilina Araujo; Carvalho, Cristiano Marcelo Espinola; Souza, Pricila Fatima de; Silva, Cristiane Bezerra da (Revista Eletrônica em Gestão, Educação e Tecnologia Ambiental, 2015)
Chia (Salvia hispanica L.) is an annual herbaceous plant native to Mexico in pre-Columbian times was used a lot with food and medicinal purpose, but during the process of domestication suffered habitat loss due to degradation of natural resources. It has high contente of omega-6 and omega-3, potent antioxidants, protein, dietary fiber, α-linoleic, widely used in weight reduction treatments, and reduction of cholesterol and its price is always high (100 g seed costs on average £ 25.00). The objective was to evaluate the production of seedlings of S. hispanica from embryos in culture media with and without sucrose. Held at 120 seed disinfection detergent Tween 80 for 2 minutes soaking in 1% sodium hypochlorite for 5 minutes in 70% ethanol for 2 min followed by rinsing three times with sterile distilled water. After this procedure, the seeds were placed in glass vials with 5 mL of liquid MS medium plus 30 g L-1 sucrose 100 mg L-inositol 1 pH adjusted to 5.8 without and without phytoregulator agar. Was used as control MS medium without sucrose and without agar. The cultures were kept in a growth chamber at 25 ± 2 ° C under a photoperiod of 16 hours. Each vial contained 30 seeds with 4 replications. We evaluated the germination and early growth of the seedling root and hypocotyl. 60 seedlings per treatment were used for evaluation of measures with a millimeter ruler on the length of the shoot and root. Germination was always higher in cultures with sucrose. Plantlets from 14 days had higher growth of shoots and roots in MS medium with sucrose. Sucrose directly affects seedling development of chia and may impair normal growth and promote somaclonal variation.